Distortion and broadening of internal solitary wavefront in the northeastern South China Sea deep basin - Jieshuo Xie; Yinghui He; Haibin Lü; Zhiwu Chen; Jiexin Xu; Shuqun Cai (Geophysical Research Letters)
Abstract Internal solitary waves (ISWs) with peculiar fronts are frequently observed in the world ocean by satellite images, though with quite few explanations. In this study a distorted and broadening ISW front across the northeastern South China Sea deep basin is presented by using synthetic aperture radar (SAR) image. To illustrate this peculiar front, a nonlinear refraction model is developed to simulate and evaluate the effects of realistic bottom topography, current, and stratification on its transformation. Simulated results in realistic oceanic environments show good agreements with this SAR‐observed front. Based on separate and comparative results in different background environments, we demonstrate that the distortion is actually caused by the strong mesoscale currents at periphery of an anticyclonic eddy. Moreover, the broadening is due to the difference in change of wave half width at different rays, which is associated with the different transformation of ISWs across variable bottom topography in the deep basin.